FAKTOR INTRINSIK DAN EKSTRINSIK YANG MEMPENGARUHI TINDAKAN IBU HAMIL MELAKUKAN VAKSIN COVID-19 - Widia Lestari; Erika Erika; Yulia Irvani Dewi; Sri Utami; Masrina Munawarah Tampubolon; Viviandra Seroja (Fakultas Keperawatan, Universitas Riau, 2023)
The achievement of COVID-19 vaccination for pregnant women in Riau Province is still relatively low. Many factors influence pregnant women not to get the vaccine, both internal and external factors. This study aims to identify intrinsic and extrinsic factors that influence pregnant women's actions in carrying out the COVID-19 vaccination. The research design used is a cross-sectional study approach that simultaneously measures and collects the independent and dependent variables found in the research object. This research was conducted in the working area of the Umbansari Rumbai Public Health Center, Pekanbaru City. The population in this study was all pregnant women in the working area of the Umbansari Health Center for the period December 2021 to July 2022. The sampling technique in this study was purposive sampling with inclusion criteria: pregnant women in the second and third trimesters; mothers in good physical and mental health; pregnant women who live in the working area of the Umbansari Health Center. Based on this, the sample in this study amounted to 78 respondents. The statistical test used is the chi square, which is used to test whether or not there is an influence between the two variables. The results showed that the perceptions of pregnant women about the COVID-19 vaccine were balanced between positive and negative; information from health workers was adequate (60.3%); family support was low (73.1); and information from social media was negative (58.97). Statistical tests were obtained for perception (Pv = 0.005), information from health workers (Pv = 0.019), family support (Pv = 0.005), and information from social media (Pv = 0.039). Conclusion: Both intrinsic and extrinsic factors have been proven to influence pregnant women to get the COVID-19 vaccine. Suggestion: Health workers are more intense in providing information about the COVID-19 vaccine through social media.